Child Rights In The Context Of Islamic Family Law - YÜKSEK, Ali (Scientific Journal of Faculty of Theology, 2022)
In Islamic law, the period that begins with birth and continues until adolescence is called “childhood”. Childhood has its own phases. The child has some rights and duties from the time he falls into the mother's womb until he is a teenager. Rights and duties regarding children are guaranteed in Islamic law and positive law. Rights such as the right to life, the right to surname, the right to citizenship start from the fetal period, provided that they are born alive. In addition, children have the following rights: children's right to know their parents, relatives and surname, the right to citizenship, the right to inheritance and property, care rights such as sucking milk, good nutrition, clothing and shelter, children are valued by their elders and protected with love and compassion, rights to be protected from bad bad habits, the right to play and the right to good manners and education. Knowing and respecting children's rights also contributes to their biological and psychological development. It is necessary to respect children's rights in order for children to stay away from all kinds of violence and abuse, to be successful, harmonious and peaceful in life, and to be individuals who can contribute to social peace and trust. Families and individuals in the society should be made aware of children's rights.